2021
DOI: 10.2147/ijn.s339857
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oral Bioavailability of Epalrestat SBE7-β-CD Complex Loaded Chitosan Nanoparticles: Preparation, Characterization and in-vivo Pharmacokinetic Evaluation

Abstract: Background Epalrestat (EPL) is a carboxylic acid derivative with poor aqueous solubility and its pharmacokinetic features are not fully defined. Purpose Current research aimed to fabricate inclusion complexation of EPL with SBE 7 β-CD (IC) and EPL/SBE 7 β-CD CS NPs (NP). Methods EPL was complexed with SBE 7 β-CD using the co-precipitation method, and the prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Particle size is the most important parameter in fabricating encapsulation of G. arborea and S. pinnata aqueous extracts. Nanoparticles can cross cellular membranes when the particle diameter is small and ultimately leads to efficient dispersion of the drug [23] . The larger particle size of SAE−CS−TPP (417±86 nm) compared to CS−TPP (105±1 nm) and of GAE−CS−TPP (113±5 nm) could reflect its higher EE (68.21±0.66 %) and LC (0.79±0.17 %).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particle size is the most important parameter in fabricating encapsulation of G. arborea and S. pinnata aqueous extracts. Nanoparticles can cross cellular membranes when the particle diameter is small and ultimately leads to efficient dispersion of the drug [23] . The larger particle size of SAE−CS−TPP (417±86 nm) compared to CS−TPP (105±1 nm) and of GAE−CS−TPP (113±5 nm) could reflect its higher EE (68.21±0.66 %) and LC (0.79±0.17 %).…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticles can cross cellular membranes when the particle diameter is small and ultimately leads to efficient dispersion of the drug. [23] The larger particle size of SAEÀ CSÀ TPP (417 � 86 nm) compared to CSÀ TPP (105 � 1 nm) and of GAEÀ CSÀ TPP (113 � 5 nm) could reflect its higher EE (68.21 � 0.66 %) and LC (0.79 � 0.17 %). Similar results were observed in void nanoparticles and hydrometha l extract derived from Punica granatum L. (Family: Punicaceae or Lythraceae) fruit peel encapsulated chitosan nanoparticles.…”
Section: Encapsulation Of G Arborea and S Pinnata Aqueous Extracts In...mentioning
confidence: 98%
“…In previous studies, some important differential metabolites showed significant biological activity. Epalrestat is used to treat diabetes, kidney disease, heart disease, and retinopathy and can relieve diabetic neuropathic pain [ 33 , 34 ]. Flavin adenine dinucleotide (FAD) is an essential component of the body’s intracellular multifunctional oxidase system, involved in intracellular redox and electron transport systems in mitochondria, and associated with in vivo metabolism of sugars, fats, proteins, etc.…”
Section: Discussionmentioning
confidence: 99%
“…12 Epalrestat demonstrates limited solubility and dissolution rate, placing it in Class II of the Biopharmaceutics Categorization System categorization. 13 Hence, it is imperative to examine the diversity in absorption across various segments of the gastrointestinal tract, specifically focusing on the absence or minimal absorption occurring in the jejunum, since this may give rise to the double peak phenomenon. 14 In addition, it is worth noting that despite the use of epalrestat for managing diabetic complications, there exists a limited number of published pharmacokinetic research on this subject.…”
mentioning
confidence: 99%
“…14 In addition, it is worth noting that despite the use of epalrestat for managing diabetic complications, there exists a limited number of published pharmacokinetic research on this subject. 9,13,15 The objective of this study was to assess the bioequivalence between a novel test formulation and a reference formulation of oral epalrestat (50 mg) in a population of healthy Chinese subjects.…”
mentioning
confidence: 99%